Eating behaviour effects on health and school performance in adolescents - Duarte, João (2020)
Objectives: To identify factors associated with academic performance of adolescents, including sociodemographic variables; analyse the inluence of eating behaviour may have in predicting the quality of school performance of adolescents; and analyse the relationship these variables establish among themselves. Design: Quantitative, cross-sectional, analytical, descriptive and correlational, explanatory and retrospective study. Setting: 2nd and 3rd Cycle Basic School in the Viseu Municipality, Portugal, 2011-2012. Participants: Non-probability convenience sampling, consisting of 380 students attending 7th, 8th and 9th grades, aged between 11 and 17 years. Measurements: Data collected by direct questionnaire, with socio-demographic information, eating behaviour, and school performance scale (adapted from Fermin, 2005). Results: The prevalence of adolescents who do not have breakfast was 4.5%. Within adolescents with unhealthy diets, boys commit a higher of percentage food errors (51.3%) and more on 8th and 9th years (35.6%). Academic achievement is higher in girls (P < .001), in the younger students (P < .001) in those with a parent with secondary or higher education (P = .019) and students who have a healthy diet (P = .000). Conclusions: An inadequate eating behaviour and an unhealthy diet are associated with decreased school performance in adolescents. The implications at the individual, family and social level proves to be important to identify risk groups to develop prevention policies in the ield of nutrition education.